Daya guna dan hasil guna untuk pengendalian hama wereng coklat (Nilaparvatalugens Stal) penggunaan varietas tahan dan insektisida pada tanaman padi - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
ABSTRACT The brown planthopper (Nilaparvata lugens Stal) was known as major pest of rice in Indonesia. Result of experiment showed that IR 36 variety more resistant of the brown planthopper than Cisadane varitey. The pest control tactic by resistant varieties and insecticides applications based on the economic threshold more efficient compared with the pest control lactic by resistant varieties and insecticides based on the schedule spraying and resistant varieties without insectkied. The pest control tactic by Cisadane variety and Buprofezin based on the economic threshold was the most effective and efficient. The termination of insecticide subsidy by government perhaps could be conducted if the Integrated Pest Management system have been implementated steadily and continuously.